Social enterprises and the poor transforming wealth - Dacanay, Marie Lisa M. ([Quezon City] Institute for Social Entrepreneurship, 2013)
Revision of the author's dissertation (Ph.D.)--Copenhagen Business School, 2012.
"Key sources for case studies": pages 298-304.
Includes bibliographical references (pages 305-314).
In English.
Keywords: Social entrepreneurship -- Philippines; Poor -- Philippines; Wealth -- Philippines